RETRACTED: Measures to prevent and decrease the damage caused by anthropogenic impact on the Don river - Hijnyakova Natalia; Tkacheva Irina; Neidorf Anna; Khetsuriani Elgudja; Kokhanov Yuriy (BIO Web of Conferences)
See the retraction notice BIO Web of Conferences 138, 00001 (2024), https://doi.org/10.1051/bioconf/202413800001